ANALISIS PEMBIAYAAN BERMASALAH (NON PERFORMING FINANCING) PADA ASTRA CREDIT COMPANIES (ACC) CABANG PONTIANAK - Amelia Amelia (STIE 'INDONESIA' Pontianak, 2019)
This research was conducted to obtain what cause of overdue financing and how to overcome problems in the Astra Credit Company (ACC) Pontianak Branch. The variables of this study are single variables, non performing financing (NPF), which become indicators include External and Internal. The method used in this research is descriptive research method. The form of research is a case study. Data collection techniques are direct communication techniques, documentary study techniques. Data collection tools are interviews and archives. From the analysis in this study, the following conclusions are Inadequate human resources, Analysis at the outset of funding submissions, and East Pontianak Region which is the largest source problem